LiteratureTastes in Daoneua’s “Pharyouxivid” Novel - SYVONGSAK , Somthapheuy; SYSOUPHANH, Sangkhom; NIMNUAN , Laion; SONETHALA, Amphai (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This research is to study literature tastes inDaoneua’s “Pharyouxivid” novel. It is a qualitive study which aims to investigate love that is shown through the novel based on Maha Sila Vilavong’s theories and Males Sama’s. Analysis, explanation, interpretation and evaluation were employed as methods. The findings shows that the authors could describe various kinds of love such as love among family members: Parents’ love for children, children’s love for parents and love among siblings; love among friends: love among general friends, love among real friends; love among couples: sincere love and coercive love.Daoneua’s “Pharyouxivid” novel is a literature composition in which the authors describe the novel with great love and make readers feel emotional. Most love comes fromsincerity, love with honesty, there are different forms and genres of love. Of course, when reading or listening to them, it feels appreciatively and gets great emotion.